2020
DOI: 10.3174/ajnr.a6513
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intracortical Lesions on Volumes of Subcortical Structures in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE: Recent studies showed thalamic atrophy in the early stages of MS. We investigated the impact of intracortical lesions on the volumes of subcortical structures (especially the thalamus) compared with other lesions in MS. MATERIALS AND METHODS:Seventy-one patients with MS were included. The volumes of intracortical lesions and white matter lesions were identified on double inversion recovery and FLAIR, respectively, by using 3D Slicer. Volumes of white matter T1 hypointensities and subcor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…We completed our analysis investigating also other possible clinical and MRI variables associated to the volume loss of the thalamus, cerebellar cortex and hippocampus: in line with previous data, 35 we observed a relationship between the volume at T0 and volume change at T24 of these structures and both GM and WM lesion load and disease progression.…”
Section: Discussionsupporting
confidence: 81%
“…We completed our analysis investigating also other possible clinical and MRI variables associated to the volume loss of the thalamus, cerebellar cortex and hippocampus: in line with previous data, 35 we observed a relationship between the volume at T0 and volume change at T24 of these structures and both GM and WM lesion load and disease progression.…”
Section: Discussionsupporting
confidence: 81%
“…Abnormalities in the gray matter, whether deep or cortical, including atrophy or lesion in the cortex, can predict the progression of disability among patients with MS. Several studies have shown a strong correlation between cortical lesion and EDSS score [32][33][34][35][36][37][38] with cortical lesion volume being a predictor of neurologic disability progression during follow-up [35]. Gray matter atrophy has also been identified as a predictor of higher EDSS scores [34,39,40].…”
Section: Mri Markers Predicting the Disability Progressionmentioning
confidence: 99%
“…Indeed, if inflammation in the white matter, related to the formation of WMLs, is recognized as the major driving force for deep gray matter atrophy in early phases and a relapsing-remitting course, 7 less is known about the mechanisms sustaining the enduring subcortical volume loss in chronic disease stages and a progressive course, when neuroinflammation in the white matter becomes less pronounced, as well as its impact on subcortical atrophy and disease progression. 5 In this light, the correlation between cortical lesions and deep gray matter atrophy, reported by Kalinin et al, 6 may reflect a second-order disconnection effect via thalamocortical radiations and corticothalamic tracts, and/or it may represent an epiphenomenon related to the prominent primary involvement of gray matter (both cortical and subcortical, simultaneously), which is known to characterize chronic disease stages and progressive phenotypes. 1 Understanding the pathogenic processes underlying subcortical gray matter (primarily thalamic) atrophy in different phases of the disease would be critical in the determination of treatment strategies, potentially informing therapeutic choices with the aim of preventing the occurrence of thalamic damage and its detrimental consequences in terms of brain network economy and clinico-cognitive functioning.…”
mentioning
confidence: 96%
“…4 However, despite its pathophysiologic and clinical relevance, what drives this typical pattern of neurodegeneration in MS remains partially unclear, probably including a combination of primary local neuroinflammatory and neurodegenerative pathologic processes and secondary effects from remote injury in other parts of the brain (mainly white matter) via anterograde/retrograde degeneration and/or spreading of inflammation along axonal pathways. 5 The study by Kalinin et al, 6 published in a recent issue of the American Journal of Neuroradiology, explores the impact of purely intracortical lesions compared with white matter lesions (WMLs) on the volumes of deep gray matter structures in a cohort of patients with relapsing-remitting MS (RRMS, n ¼ 54), secondary-progressive MS (SPMS, n ¼ 12), and primary-progressive MS (PPMS, n ¼ 5). They found that patients with intracortical lesions had longer disease duration, greater disability, and more deep gray matter atrophy.…”
mentioning
confidence: 99%